The Committment and Dedication to Knowledge Occupation: Paradoxes of Platonic Relation and the Examination with Professionalism - Sağsan, Mustafa; Fırtına, Burak (Information World, 2015)
This study attempts to underline the relationship between professionalism and occupational commitment and occupational dedication in the context of platonic love for the assistant librarian in TRNC. Professionalism, which could be evaluated as a dependent variable in the study, has been divided into four categories such as responsibility of professionalism, learning of professionalism, pursuit of professionalism via social media, and solidarity of professionalism. The first independent variable, called occupational commitment, has also been divided into three forms such as emotional commitment, continuity commitment and normative commitment. There are mainly two types of occupational dedication which is the second and last independent variable of the study. These are vigor and absorption There are three important results of the empirical part of this study. (1) The responsibility of professionalism, learning of professionalism, and solidarity of the professionalism have all positively been affected by the vigor of occupational dedication for the assistant librarian in TRNC. (2). Normative commitment has negatively been affected by the following of professionalism by using social media for the assistant librarian in TRNC. (3) Emotional commitment has positively been affected by the solidarity of professionalism for the assistant librarian in TRNC. Four important recommendations have been proposed for the assistant librarians in TRNC in order to transform their platonic love to real love regarding the occupation of librarianship.